Improving the reliability of pneumatic devices for vehicles - Зубенко, Денис Юрійович (Technology audit and production reserves, 2014)
Operation of the vehicle pneumatic system on the example of two matching devices, defining transport safety – pneumatic wheel and a device, ensuring pressure and maintaining it in automatic mode – compressor is shown in the paper. New approaches to the organization of failure-free operation of these devices are proposed. New type of pneumatic wheel of a vehicle, which during the motion can provide a desired pressure in the tire, is shown. New operation principle of pneumatic compressor, based on a linear electric motor is investigated. The necessity of such developments is caused by the fact that there is a need for improving individual units of transport equipment for further reliable and failure-free operation. During the development and theoretical calculations, it was found that this trend of technical improvement allows to increase efficiency and provide longer service life while increasing reliability. This area of technical developments is important to create a new generation of transport equipment, which will allow to operate at higher speeds and at much higher loads, as well as at minimum operating and repair costs.